The Used of Video Tracking for Developing a Simple Virtual Boxing - David Habsara Hareva; . Martin (International Conference on Engineering and Technology Development (ICETD), 2012)
Now, video tracking is a feature that used a lot in computer gaming. This feature makes games more interesting because it offers direct interaction between the player and computer while in the same time player can exercise his/her body and eye coordination. For this reason, implementing video tracking in virtual boxing is a challenging task. Compared to the standard computer game controllers, controlling game using video tracking is more appealing and attractive. The aimed is to explore the used of video tracking at developing a simple virtual boxing. In this study the used method for detecting object such punch types was a Mean-shift method. This detection was done based on the moving area of the object’s surfaces, thus this information could be used to differentiate punches type, which is classified as Jab, Hook, and Uppercut. The making of Virtual Boxing comprises of video tracking development and gaming design. This development of virtual boxing involves a number of configurations such as webcam configuration, color tolerance setting in the detector, and tolerance of the color detection. Every video tracking modification and gaming design is evaluated thoroughly. All of configuration was evaluated to ensure that this virtual boxing meet the initial expectation. The result shows that the punch detection reading in using library color tracking using Mean-shift in a boxing game is good enough, but wasn’t perfect yet. The Mean-shift method needs to be combined with other method in order to detect punches perfectly.